Universidade corporativa: implicações na trajetória profissional e perspectivas para a educação ao longo da vida - Correia, Adriana Merceslane Morais (2018)
Between the years 1920 and 1930, were born the first universities, that evolved from the various attempts for it creation. The brazilian economy also developed, influenced by globalization, for development on a global scale and by new technologies. The communication between people, countries, computers and organizations intensified, resulting in a restructuring of the productive chain. The formation of human resources affected by the appearance of new demands and new professions. There was a break in the linearity of careers allied to the great oscillations of the market, the modern needs of qualifications and the requirements for the formation of the professional contemporary, who spent to experience more than one activity during your life. Therefore, the Unesco (United Nations Educational, Scientific and Cultural Organization), recommends that education have to prolong for all life. In this perspective, the corporate universities emerged to attend the immediate needs of competencies and abilities to carry out the work tasks, and the literature recommends that they have as the fundamental principle the development of employees in all posts and hierarchicals levels. The objective this work is investigate which the contributions of the corporate university of Bank of Brazil in the process of improvement its users as part of lifelong education. The method used is the case study of qualitative nature, exploratory character. For constitution of data it was considered the bibliographical research, stands out the history of the university in Brazil, the establishment of the information society and the principles of lifelong education resulting from Unesco reports. In documentary research, it emphasize the printes Itineraries on the Bank of Brazil and consultation of the institution's public documents. The semi-structured interviews were carried out after previous approval of legal responsibilities of the corporation and written consent of the interviewees. We consulted 10 employees, between 4 and 31 years of company, in various levels and functions. The analysis and interpretation of the data were realized through constructing categories based on the Bardin Content Analysis technique (2016). The most tendency significant, perceived in interviews, was that the corporate university contributes positively to the process of learning and knowledge management of employees, however, some gaps, as a targets enforcement system and the speed of contents updating points out the need for reflections on the part of its managers. We recognize the relevance of the Corporate University Bank of Brazil, overcoat in the process of lapidation of competence required for the dynamics of work of the employees, expanded by the incorporation of precepts civilizing training, ethical and cultural, also available to the general public, relatives of employees and retirees which are in line with the assumptions of lifelong education defended by Unesco in its reports. As contribution, this production presents questions that should be object of consideration and analyses by the managers of the university reason for this study, as for organizations that have corporate university and intend to improve them.